CONTRASTING THOUGHTS: INTERNALIZATION OF ISLAM WASATIYAH OF DAYAH ULAMA IN GROUNDING MODERATE ISLAM IN PESANTREN - Anzaikhan, M.; Muarrif, Muhammad Riza; Bahri, Syamsul; Sufrizal, Sufrizal; Umam, Chatibul (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This research explains the change of contrasting thoughts in pesantren (an Islamic boarding school), which is indicated as radical and terrorist in Aceh Tamiang. Ulama's thoughts and concepts of Pesantren Al-Hidayah influenced the changes after undergoing guidance from the government. This article is field research with a qualitative approach. A case study and phenomenological study were used as the methodology. The research results concluded that the internalization of Islam Wasathiyah at Pesantren Al-Hidayah contained seven themes, including Environmental Islam, Al-Musawat and AlTawazun (justice), AsSamahah (tolerance), Shura (deliberation), Islah and Ihsan (reconciling), Qudwah (role model), and Muthwathanah (nationalism).